Hemodynamic Consequences of Hypertrophic Cardiomyopathy with Midventricular Obstruction: Apical Aneurysm and Thrombus Formation - Saba, Shahryar G (J Gen Pract (Los Angel), 2014)
BACKGROUND: Hypertrophic cardiomyopathy (HCM) with midventricular hypertrophy is an uncommon phenotypic variant of the disease. Midventricular hypertrophy predisposes to intracavitary obstruction and downstream hemodynamic sequelae. CASE REPORT: We present a case of HCM with midventricular hypertrophy and obstruction diagnosed after a CT scan of the abdomen incidentally revealed a filling defect in the left ventricular apex. Transthoracic echocardiography demonstrated mid left ventricular hypertrophy and obstruction, as well as an aneurysmal apex containing a large thrombus. Cardiovascular MRI showed a spade-shaped left ventricle with midcavitary obliteration, an infarcted apex and regions of myocardial fibrosis. Due to the risk of embolization and a relative contraindication to anticoagulation, the patient underwent surgery including thrombectomy, septal myectomy and aneurysmal ligation. CONCLUSIONS: Hypertrophic cardiomyopathy with midventricular hypertrophy leads to cavity obstruction, increased apical wall tension, ischemia and ultimately fibrosis. Over time, patchy apical fibrosis can develop into a confluent scar resembling a transmural myocardial infarction in the left anterior descending coronary artery distribution. Aneurysmal remodeling of the left ventricular apex potentiates thrombus formation and risk of cardioembolism. For these reasons, hypertrophic cardiomyopathy with midventricular obstruction portends a particularly poor prognosis and should be recognized early in the disease process.